Translating Local Knowledge at Organizational Peripheries - Yanow, Dvora (British journal of management, 2004)
This article theorizes about the kinds of knowing present in organizations that share both a structural similarity in the organization of work and work practices – a ‘double periphery’ in which a community of practitioners acts across both a horizontal, geographic periphery and a vertical, hierarchical periphery – and a common mode of practice – translating across these peripheral borders. In principle, these workers develop knowledge in interaction with clients and customers that could be valuable to the organization, were it but to learn from them. Instead, the ‘local knowledge’ they learn in acting across these peripheries is discounted, if not disparaged, by more centrally‐located managers and executives. The article theorizes about the nature of translating local knowledge concerning organizational practices and about the structural character of local versus ‘expert’ knowledge.